PENGARUH TINGKAT PENGUNGKAPAN SUKARELA TERHADAP NILAI PERUSAHAAN - Lupita Ade Arisanti,; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of the level of voluntary disclosure on firm value. The dependent variable of this study is the value of the company as measured by market kapitlisasi value and market value to book value. The independent variable of this study is the level of voluntary disclosure as measured by the 96 index voluntary disclosure that are divided into 12 categories. This study uses five control variables, namely leverage, net income, growth, ROA and size. The population in this study is the entire manufacturing companies listed in Indonesia Stock Exchange in 2011. Sampling method in this study is purposive sampling. Criteria for the company is that the company's market capitalization to convey information in the annual report in the report tahunanya his company and also the company revealed the variables needed in the study sample. The total amount of the final sample in this study was 86 companies. After going through the stages of processing and data. The analysis technique used is an OLS regression (Ordinary Least Square). The analysis showed that the independent variables are the level of voluntary disclosure has a positive and significant impact on the value of his company.